Dramatic improvement in the stability and mechanism of high-performance inverted polymer solar cells featuring a solution-processed buffer layer. Issue 7 (25th January 2023) - Sung, Yun-Ming; Chang, Cheng-Hsun-Tony; Tsao, Cheng-Si; Lin, Hua-Kai; Cha, Hou-Chin; Jiang, Pei-Cheng; Liu, Tian-Cheng; Chang, Kang-Wei; Huang, Yu-Ching; Tsay, Jyh-Shen
Abstract : In this study, we demonstrate inverted PTB7:PC71 BM polymer solar cells featuring a solution-processed s-MoO3 hole transport layer that can, after thermal aging at 85 °C, retain their initial power conversion efficiency for at least 2200 h. Abstract : In this study, we demonstrate inverted PTB7:PC71 BM polymer solar cells (PSCs) featuring a solution-processed s-MoO3 hole transport layer (HTL) that can, after thermal aging at 85 °C, retain their initial power conversion efficiency (PCE) for at least 2200 h. The T 80 lifetimes of the PSCs incorporating the novel s-MoO3 HTL were up to ten times greater than those currently reported for PTB7- or low-band-gap polymer:PCBM PSCs, the result of the inhibition of burn-in losses and long-term degradation under various heat-equivalent testing conditions. We used X-ray photoelectron spectroscopy (XPS) to study devices containing thermally deposited t-MoO3 and s-MoO3 HTLs and obtain a mechanistic understanding of how the robust HTL is formed and how it prevented the PSCs from undergoing thermal degradation. Heat tests revealed that the mechanisms of thermal inter-diffusion and interaction of various elements within active layer/HTL/Ag electrodes controlled by the s-MoO3 HTL were dramatically different from those controlled by the t-MoO3 HTL. The new prevention mechanism revealed here can provide the conceptual strategy for designing the buffer layer in the future. The PCEs of PSCs featuring s-MoO3 HTLs, measured in damp-heat (65 °C/65% RH; 85 °C per air) and light soaking tests, confirmed their excellent stability. Such solution-processed MoO3 HTLs appear to have great potential as replacements for commonly used t-MoO3 HTLs.